Palladium N‐Heterocyclic Carbene Catalysts for the Ultrasound‐Promoted Suzuki–Miyaura Reaction in Glycerol. Issue 6 (8th April 2013) - Azua, Arturo; Mata, Jose A.; Heymes, Pauline; Peris, Eduardo; Lamaty, Frederic; Martinez, Jean; Colacino, Evelina
Abstract Novel palladium N‐heterocyclic‐carbene (NHC)‐based complexes with 3, 4, 5‐trimethoxybenzyl, alkyl and sulfonate N‐substituents were obtained and fully characterized. The new complexes were used as pre‐catalysts in the Suzuki–Miyaura coupling of various aryl halides/boron sources in glycerol under pulsed‐ultrasound (P‐US) activation. High yields were obtained under mild reaction conditions, without formation of undesired by‐products. The pure final cross‐coupling products were easily recovered without column chromatography and the catalytic/solvent system could be recycled. TEM (transmission electron microscopy) and XPS (X‐ray photoelectron spectroscopy) were used to characterize the nanoparticles and to investigate the fate of the catalysts.